Aesthetic logics, terroir and the lamination of grower champagne. Issue 1 (2nd January 2021) - Smith Maguire, Jennifer; Charters, Steve
ABSTRACT: This paper examines how aesthetic institutional logics and objects shape markets. We focus on the champagne field, for which dominant category conventions include luxury, celebration and protected regional origin (exemplified by grande marque champagne). Our attention, however, is on more recent, alternative conventions, such as site-specific terroir and passionate artisanality (exemplified by "grower champagne"). In analyzing how trade associations, small-scale producers and wine writers represent champagne, we offer an approach that is sensitive to both top-down and bottom-up dynamics of logics. Drawing on the concept of lamination to provide a processual bridge between category conventions and institutional objects (and thus logics), we find that representations from the three actor groups build up – layering and (at least partially) overlapping – such that both dominant and alternative frames come to shape the champagne field. We suggest how divergent representational practices may be directed at and by a common aesthetic institutional object.